Happiness Differences among University Students Living with Family and Those Living Alone - Tobing, Pelita Debora Karen Lumban; Dewanti, Yunita; Maulani, Nabilah Maghfirah; Halida, Rizka (Journal of Family Sciences, 2025)
Urban issues, particularly in the context of university students, were shaped by factors such as the type of residence, mode of transportation, and social interactions, which influenced their daily lives and decisions regarding privacy, freedom, and convenience. This study explored how the type of residence influences the happiness of university students, focusing on students living with their families versus those living independently. Using a descriptive qualitative method with semi-structured interviews, four students aged 23–30 years were interviewed.  The data were analysed thematically, with the PERMA theory serving as a conceptual framework to understand the participants' experiences. Findings showed that students living with their families experience higher happiness levels due to stronger social support, which fostered positive emotions and a sense of meaning in their daily lives. In contrast, students living independently faced more challenges and limited social support, requiring extra effort to achieve acceptance and happiness. The key factors influencing happiness for both groups included the form of social support, engagement in daily activities, and the meaning attributed to challenges. Students living with their families received more support through direct interactions, while those living independently relied on support from significant others outside their residence. Despite differences in support sources, both groups demonstrated resilience and meaning-making strategies that contributed to their happiness. The study highlighted the importance of social support and individual coping strategies in shaping students' well-being.